Fiber-optic bronchoscopy for diagnosing hilar masses of the lung: a study from a tertiary care cardiothoracic and vascular centre in northeastern India - James Thiek; Mrinmoy Talukdar; Akash Guha (Journal of Current Oncology and Medical Sciences)
Introduction: Fiberoptic Bronchoscopy is an important tool at a clinician's disposal for managing various pulmonary pathologies both benign and malignant. Its sensitivity and specificity highly depend on the site of the pulmonary lesion with central lesions providing better results than peripheral ones. The procedure is usually well tolerated if done properly with most complications being amendable to conservative management. Specially for hilar masses of the lung bronchoscopy not only allows for obtaining biopsy tissue but also evaluation of the anatomy for operative planning.